Rising epidemic of COVID-19 in India – knowledge, attitude and practices among general population - Monya, Michi; Chaudhari, Yasmeen (International Journal Of Community Medicine And Public Health, 2021)
Background: Coronavirus disease 2019 (COVID-19) is an emerging disease caused by a novel corona virus, Severe Acute respiratory syndrome coronavirus 2 (SARS CoV2). It was first detected in December 2019 in Wuhan, China. The rapid spread and the novel nature of the disease has created an environment of confusion and panic among people. Methods: A cross-sectional study was conducted using web-based questionnaire in different languages, the link of the online questionnaire shared as text message was shared/posted/reposted through author’s social media accounts and e-mails. It consisted two parts: Demographic details and KAP containing total 19 questions (K-13, A-3, P-3). Data analysis was conducted using SPSS-20 statistical software. Results: It was found that higher education level has associated significantly with higher knowledge score (β= -0.213: p=0.00). Multiple regression analysis showed that attitude of people avoiding Chinese restaurants was significantly associated with younger age group (Expβ=0.975: p=0.021). The practice of wearing mask while leaving home was found significantly associated with education (p=0.024) and occupation (p=0.000) in univariate analysis. Similarly, the practice of washing hands was significantly associated with age in both univariate (p=0.049) and multivariate analysis (Expβ=0.932: p=0.049). Conclusions: The practice of majority of Indian residents was very cautious. But correct response rate for knowledge score was only 72.54% and positive attitude about COVID-19 control in India was demonstrated by 74.18% respondents, thus reflecting inadequate information about COVID-19 and lower confidence on its control. Information, education and communication (IEC) campaigns by various sources needs to be optimized across various sociodemographic groups to address those at higher risk.